AB1187-HPR Rheumatologist and Rheumatology Health Care Professionals' Current Practice and Beliefs around Physical Activity Promotion in Rheumatoid Arthritis. (10th June 2014) - Flanagan, S.; Kennedy, N.; Kelly, G.
Abstract : Background: Regular physical activity (PA) in rheumatoid arthritis (RA) is beneficial for people with RA (Van Den Ende et al 2000). However, people with RA are less physically active than their healthy peers (Sokka et al 2008). Currently very little is known about physical activity prescription/promotion by rheumatologists and rheumatology health care professionals (HCP) within the RA population in Ireland. Objectives: Examine rheumatologist and rheumatology HCP beliefs, current practices, perceived competence and educational needs on the promotion of PA in RA. Methods: An online questionnaire-based survey was distributed to members of the Irish Society of Rheumatology (ISR) (n=97) and the Irish Rheumatology Health Professionals Society (IRHPS) (n=30). The questionnaire was researcher-designed for the purpose of the study and consisted of 17 questions. SPSS (version 21) were used to analyze the data using descriptive statistics and Kruskal-Wallis tests to examine differences between the 3 groups. Results: Sixty-four HCP responded (response rate 50% (n=64) (rheumatologists n=35, 15 nurses (n=15) physiotherapists (n=8)). The majority of respondents believe that PA is both attainable (100% rheumatologists, 93% nurses, 100% physiotherapists) and safe (97% rheumatologists, 100% nurses and physiotherapists) for patients with RA. Advice on PA was always or regularly given by almost 100% of each profession. A minority of rheumatologists and nurses regularly advised PA for those with a high disease activity (rheumatologist 31%, nurses 20%) while just half of physiotherapists (50%) did so. Safety concerns were raised with 40% of rheumatologists and 27% of nurses indicating that regular PA was unsafe for patients with a high disease activity. Very few nurses (7%) and rheumatologists (17%) regularly used public health recommendations when giving PA advice in comparison to the three quarters (75%) of physiotherapists reporting that they do. A number of barriers to PA were identified including multiple co-morbidities, high disease activity and lack of engagement by the RA patient. The majority (rheumatologists 83%, nurses 93% physiotherapists 100%) indicated interest in further education on PA promotion. *: (Rheumatologist group included consultant rheumatologists, rheumatologists in training and 2 research registrars) Conclusions: PA for people with RA is considered safe by the majority of rheumatologists, nurses and physiotherapists who specialise in rheumatology. For patients with high disease activity PA is seen as a more unsafe and less important health goal. There is a high demand for further education on PA promotion in people with RA. References: Sokka, T., Häkkinen, A., Kautiainen, H., Maillefert, J. F., Toloza, S., Calvo-Alen, J. and Pincus, T. (2008) Physical inactivity in patients with rheumatoid arthritis: Data from twenty-one countries in a cross-sectional, international study. Arthritis Care & Research, 59(1), 42-50. Van den Ende, C. H. M., Breedveld, F. C., Le Cessie, S., Dijkmans, B. A. C., De Mug, A. W. and Hazes, J. M. W. (2000) Effect of intensive exercise on patients with active rheumatoid arthritis: a randomised clinical trial. Annals of the Rheumatic Diseases, 59(8), 615-621. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3296